2020
DOI: 10.1016/j.prro.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Severe Lymphopenia During Chemoradiation Therapy for Esophageal Cancer: Development and Validation of a Pretreatment Nomogram

Abstract: Introduction: In patients with esophageal cancer, occurrence of severe radiation-induced lymphopenia during chemoradiation therapy has been associated with worse progression-free and overall survival. The aim of this study was to develop and validate a pretreatment clinical nomogram for the prediction of grade 4 lymphopenia. Methods and Materials: A development set of consecutive patients who underwent chemoradiation therapy for esophageal cancer and an independent validation set of patients from another insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
7
46
0
Order By: Relevance
“…Multivariate analysis identi ed low TLC and high NLR before the treatment as predicting inferior survival. In recent preclinical study, the grade 4 lymphopenia seemed to predict the worse progression-free and overall survival in esophageal cancer cohort (17) . In this study, we demonstrated that pretreatment NLR and ALC nadir during de nitive RT were signi cantly associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Multivariate analysis identi ed low TLC and high NLR before the treatment as predicting inferior survival. In recent preclinical study, the grade 4 lymphopenia seemed to predict the worse progression-free and overall survival in esophageal cancer cohort (17) . In this study, we demonstrated that pretreatment NLR and ALC nadir during de nitive RT were signi cantly associated with worse outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Taking into account the negative effect of LP on clinical outcomes, it is important to identify high-risk patients timely and possibly adapt the treatment. Models predicting grade 4 RT-induced LP during chemo (radio) therapy for esophageal cancer, or acute and late LP for prostate cancer have already been published, 70,71 although the prostate model is yet to be validated. 19,72 Also for NSCLC, a predictive risk model has been developed where clinical and genetic factors, for example, lung V5 > 48%, age >65 years, >40 pack-years, and XRCC1 rs25487 AA genotype, are associated with severe RT-induced LP.…”
Section: Modelling Approaches To Predict the Incidence And Severity Omentioning
confidence: 99%
“…For esophageal cancer chemoradiation, higher spleen dose is associated with a higher risk of lymphopenia in one study and lower toxicity in another ( 11 , 12 ). Distal esophageal cancers and larger irradiated volumes are more likely to have severe lymphopenia, suggesting lower dose to normal tissue may matter ( 13 , 14 ). Lymphopenia is also associated with lower survival ( 13 ).…”
Section: Spleen As Innocent Bystandermentioning
confidence: 99%
“…Distal esophageal cancers and larger irradiated volumes are more likely to have severe lymphopenia, suggesting lower dose to normal tissue may matter ( 13 , 14 ). Lymphopenia is also associated with lower survival ( 13 ). Similar data are emerging in pancreatic cancer chemoradiation ( 15 18 ), with lower rates of lymphopenia using stereotactic body techniques ( 19 , 20 ).…”
Section: Spleen As Innocent Bystandermentioning
confidence: 99%
See 1 more Smart Citation